A Multimodal Discourse Analysis of the Interactive Meaning in Public Service Advertisement - Liu, Shuting (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
On the basis of Kress and van Leeuwen’s Visual Grammar based on Halliday’s Systemic Functional Linguistics, this study explores the interactive meaning in three public service advertisement multimodal discourses, adding evidence to the assumption that Systemic Functional Linguistics can be applied to the multimodal discourse analysis of public service advertisement in a feasible and operational manner.